POLITICAL CORRUPTION AS A CAUSE OF THE INEFFECTIVENESS OF ANTI-CORRUPTION POLICY AND A THREAT TO THE NATIONAL SECURITY OF UKRAINE - Mik, Taras (Public Management and Policy, 2026)
The article examines the problem of political corruption as a systemic factor reducing the effectiveness of state anti-corruption policy and as a threat to the national security of Ukraine. The approaches to the formation of anti-corruption policy in Ukraine remain insufficiently systematic, which is reflected in the fragmented nature of decisions, incomplete consideration of previous experience, and limited analysis of alternative instruments of state influence. Particular attention is paid to the social dimension of corruption. It is noted that corruption in Ukraine is consistently perceived as one of the key social problems, while the greatest concern is associated specifically with political corruption related to the activities of public authorities, political parties, and state decision-making processes. At the same time, everyday corruption practices are often not perceived by the population as critically dangerous, which is due to the low level of trust in state institutions and the historical peculiarities of their development. The content of political corruption is clarified as a form of improper use of public authority, administrative, and political resources for the purpose of obtaining private or group benefits. Its direct connection with the processes of public policymaking, distribution of public resources, and the functioning of key state institutions is established, which determines its systemic nature and distinguishes it from other forms of corruption. It is substantiated that political corruption has a multidimensional impact, in particular leading to reduced effectiveness of public administration, distortion of economic mechanisms, weakening of social trust, and increasing risks to national security. It is demonstrated that the effectiveness of anti-corruption policy largely depends on the quality of information support in the decision-making process. Emphasis is placed on the need to use complete, reliable, and verified statistical and sociological data for identifying corruption risks, assessing their scale, and determining priorities for state response. Based on the conducted analysis, it is determined that counteracting political corruption requires a comprehensive approach, including ensuring transparency of electoral processes, institutional separation of politics and business, strengthening the independence of the judiciary, developing public oversight, and fostering a sustainable culture of intolerance toward corrupt practices.